From the “divine kiss” to the royal decree of the Lagids: πρόσταγμα, a case of vocabulary transfer in the Greek Bible - Dogniez, Cécile (Semitica et Classica, 2024)
Abstract The aim of the present paper is to reconsider the use of the Greek word πρόσταγμα by the Septuagint translators. In the papyrological documentation of the Hellenistic period, this term generally designates the royal decree of the Ptolemies. In the Septuagint it is used, along with other Greek words, to render several terms of Hebrew law. In particular, the paper focuses on the exceptional use of πρόσταγμα as an equivalent of the Hebrew word for “mouth” in the Hexateuch, which bears implications for the transfer of this Greek word from the legal system of Lagid Egypt to the Greek version of the Hebrew Bible. Abstract Cette contribution se propose de revenir sur l’emploi du mot grec πρόσταγμα chez les traducteurs de la Septante. Dans la documentation papyrologique de l’époque hellénistique, ce terme désigne généralement l’ordonnance royale des Ptolémées. Dans la Septante il est employé, à côté d’autres mots grecs, pour rendre plusieurs termes de loi hébreux. Il importera ici de mettre l’accent sur l’emploi exceptionnel de πρόσταγμα comme équivalent du mot hébreu « bouche » dans l’Hexateuque et de voir quels sont les enjeux du transfert de ce mot grec du système judiciaire de l’Égypte lagide dans la version grecque de la Bible juive.